Solving real world security problems hacking and protection : a knowledege-based open-source online firmware security tools evaluation - Kang, Wei Bin (Nanyang Technological University, 2021)
With the advancement in technology and internet access around the globe, everything is connected with devices (IoT, smart devices, gadgets, systems) around us to make life easier. This achievement in technology has given access to cyber criminals to attack critical devices and gain unauthorized access to achieve a goal. The IoT device's firmware is placed below software and difficult to ensure security without a dedicated solution. IoT device manufacturers have advantages in adding these security solutions to their firmware, including regularity compliance, integrated security by ensuring operations, management, and security monitoring. Open-source firmware security tools help to analyse and identify the security gaps in software or web applications. This also resolves the vulnerabilities, loopholes, and loose ends in a code or application. The objective of the evolution of open-source firmware security tools is to provide all users with knowledge of framework and security concerns, as well as easy access to secure device framework testing tools, so that they can easily perform all these activities to secure device frameworks and ensure framework security best practices.